Effect of Insulin Injection Coaching Program on Self-Efficacy in Insulin Injection of Uncontrolled Diabetes Mellitus in Patients with Type 2 Diabetes - Phetpan, Nualjan; Siriphan, Siriphan; Rakpanusit, Thaparat (Princess of Naradhiwas University Journal, 2026)
Background and Objective Type 2 diabetes mellitus (T2DM) represents a chronic metabolic disease manifested by sustained hyperglycemia, primarily driven by impaired insulin sensitivity and action. These include acute complications such as infections, and long-term complications affecting various body systems. To prevent or delay the onset of these complications, insulin coaching and self-administered insulin therapy are crucial for diabetic patients. This quasi-experimental study aimed to investigate the effects of an insulin injection coaching program on the ability of patients with uncontrolled type 2 diabetes mellitus to self-administer insulin. Methods The sample consisted of 52 patients with type 2 diabetes mellitus, divided into an experimental group and a control group, with 26 participants in each group. The research instruments included an insulin injection coaching program for type 2 diabetes patients with uncontrolled blood sugar levels. The data collection tools consisted of a general information questionnaire, a health information questionnaire, and an insulin injection capability assessment, with a Cronbach’s alpha reliability coefficient of 0.81. Data were analyzed using descriptive statistics, paired t-test, independent t-test, and Chi-square test. Results The results of the study revealed that the experimental group had a higher mean score for insulin injection ability after receiving the insulin injection coaching program (x̄ = 68.73, S.D. = 4.39) than before the experiment (x̄ = 54.96, S.D. = 2.97), with statistical significance at the .05 (t = 13.721, p < .05). Conclusion and Recommendations The findings of this study showed that this program can be used to promote and enhance insulin injection skills and ability more effectively.